2022
DOI: 10.3389/fphys.2022.916323
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental analysis of three-dimensional choroidal vascularity and thickness of myopic eyes in young adults using SS-OCTA

Abstract: Purpose: We aimed to investigate the change of three-dimensional (3D) choroidal thickness (ChT), choroidal vessel volume (CVV), and choroidal vessel index (CVI) in young myopic adults using swept-source optical coherence tomography angiography (SS-OCTA) and compare the difference of these indicators in different quadrants of the macula and optic disc.Methods: A total of 248 eye samples from 135 participants were used in this cross-sectional study. Each participant underwent detailed history taking and ocular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Images with poor scan quality (less than 7/10 signal strength index), motion artefact, segmentation artefact or focal signal loss were excluded. The VG200's van Gogh software uses artificial intelligence algorithms (Chen et al, 2022; Luo et al, 2022) to identify the contours of the large and medium choroidal vessels in the B‐scans and then forms the morphology of vessels through three‐dimensional reconstruction to realize quantification of the large and medium choroidal vessels. It is a three‐dimensional index that reflects the volumetric choroidal vascularity density.…”
Section: Methodsmentioning
confidence: 99%
“…Images with poor scan quality (less than 7/10 signal strength index), motion artefact, segmentation artefact or focal signal loss were excluded. The VG200's van Gogh software uses artificial intelligence algorithms (Chen et al, 2022; Luo et al, 2022) to identify the contours of the large and medium choroidal vessels in the B‐scans and then forms the morphology of vessels through three‐dimensional reconstruction to realize quantification of the large and medium choroidal vessels. It is a three‐dimensional index that reflects the volumetric choroidal vascularity density.…”
Section: Methodsmentioning
confidence: 99%
“…The choroidal lumen area in each B-scan was identified automatically by a deep learning algorithm, as performed in previous studies (Figure 3) and the superior and inferior boundaries of the choroid were also identified automatically (Figure 3). [22][23][24] Additionally, three-dimensional reconstruction was performed to calculate the choroidal lumen volume (3D-CVV) and total choroidal volume (TCV). The three-dimensional choroidal vascular index (3D-CVI) was defined as the ratio of the choroidal luminal volume (LV) to the TCV, which was also calculated automatically by the built-in software.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, most CVI was obtained studies are quantitative research on the two-dimensional choroidal vascular index, which is based on the calculation of a single optical coherence tomography (OCT) B-scan obtained through the fovea or a selected location. However, due to the topographical changes of the choroid, this index cannot fully represent the changes in the choroidal vascular structure [13]. Therefore, the threedimensional or volumetric information of the choroid should be used to accurately evaluate choroidal vessels, such as the three-dimensional choroidal vessel index (3D-CVI) [14].…”
Section: Introductionmentioning
confidence: 99%